2021
DOI: 10.1111/pce.14223
|View full text |Cite
|
Sign up to set email alerts
|

cis‐prenyltransferase 3 and α/β‐hydrolase are new determinants of dolichol accumulation in Arabidopsis

Abstract: Dolichols (Dols), ubiquitous components of living organisms, are indispensable for cell survival. In plants, as well as other eukaryotes, Dols are crucial for post‐translational protein glycosylation, aberration of which leads to fatal metabolic disorders in humans and male sterility in plants. Until now, the mechanisms underlying Dol accumulation remain elusive. In this study, we have analysed the natural variation of the accumulation of Dols and six other isoprenoids among more than 120 Arabidopsis thaliana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…S7). The transcription of the MVA and MEP pathway genes: HMGR1 , HMGR2 , MVK , DXS , DXR , MCT , as well as of two FPP synthase genes: FPPS1 and FPPS2 , and of genes for the two final enzymes of Dol biosynthesis: CPT3 (Gawarecka et al, 2022) and PPRD2 (Jozwiak et al, 2015), remained at wild-type levels. Slight, but non-significant, induction was observed only for EVN which encodes a dolichol kinase (Lindner et al, 2015).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…S7). The transcription of the MVA and MEP pathway genes: HMGR1 , HMGR2 , MVK , DXS , DXR , MCT , as well as of two FPP synthase genes: FPPS1 and FPPS2 , and of genes for the two final enzymes of Dol biosynthesis: CPT3 (Gawarecka et al, 2022) and PPRD2 (Jozwiak et al, 2015), remained at wild-type levels. Slight, but non-significant, induction was observed only for EVN which encodes a dolichol kinase (Lindner et al, 2015).…”
Section: Resultsmentioning
confidence: 98%
“…atg mutants display early leaf senescence in response to various nutrient-limiting conditions (reviewed by Chen et al, 2019). Increasing dolichol levels have long been considered a marker of aging in animal tissues (Chojnacki & Dallner, 1988; Parentini et al, 2005), and in plants dolichol levels are also known to increase with age (Gawarecka et al, 2022). Interestingly, the recent work of Choi et al (2023) shows that a defect in the functioning of retrograde transport from the Golgi apparatus can be the primary cause of both premature leaf senescence and enhancement of the glycosylation machinery – in line with our results which show similar effects of a primary dysfunction of the ER.…”
Section: Discussionmentioning
confidence: 99%
“…They also undergo elongation to form Prens, which subsequently serve as substrates for ER-associated polyprenol reductase (PPRD2) [ 11 ]. This implies that CPT7 [ 19 ] and CPT3 [ 12 ] function independently to form Prens and Dol in Arabidopsis, similarly to the role played by two distinct CPTs in spinach leaves [ 78 ]. Such a tentative model satisfactorily explains that upon D-DX feeding, Dol-16 isotopologues in leaves are built either solely of unlabeled or labeled isoprene units.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has revealed that leaves of Arabidopsis thaliana contain a family of Prens composed of 9 to 11 isoprene units (Pren-9 to Pren-11) synthesized by CPT7. The Dol spectrum in A. thaliana (studied in hairy roots) comprises two main families: medium-length Dols (Dol-15, -16 and -17, synthesized by CPT3 [ 12 ]) and longer ones (Dol-20 to Dol-24, produced by CPT1 [ 13 ]), all of which are accompanied by traces of corresponding Prens [ 14 ]. The composition of polyisoprenoid mixtures is believed to be regulated by tissue-specific expression of dedicated CPT(s); in the Arabidopsis genome nine potential members of this multigene family have been identified [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst many genes involved in plant metabolism pathways have been identified and cloned through large-scale GWAS, there are some examples of smaller-scale studies achieving good results. For example, the pathways of saiginols (phenylacylated flavonols) ( Tohge et al ., 2016 ) and dolichols in Arabidopsis ( Gawarecka et al , 2022 ), lignin precursors in Arabidopsis, maize, and poplar ( Vanholme et al , 2019 ), and steroidal glycoalkaloids in solanaceous species ( Schwahn et al , 2014 ) have all been refined by comparisons of only a handful up to around 100 genotypes. In principal, mapping of an unknown compound to a gene gives hints as to the structure of that compound, especially in cases where the gene encodes an enzyme involved in the biosynthesis pathway.…”
Section: Use Of Populations In Metabolite and Gene Annotationmentioning
confidence: 99%